Fermatean neutrosophic rough set - S Bhuvaneshwari; C Antony Crispin Sweety; R Sumathi (Computational Algorithms and Numerical Dimensions)
In order to balance uncertainty, a reasonable approximation of a crisp set that yields lower as well as upper approximations of the set is made. Here, first, a special class of Fermatean Neutrosophic Set is devised by associating the Neutrosophic Set with the Fermatean Fuzzy Set. A relatively new concept of Fermatean Neutrosophic Approximation Space and Fermatean Neutrosophic approximation operators are introduced. In this context, a new class of Fermatean Neutrosophic Rough set is established, and a few of its characteristics are mentioned. Also, the cut sets of Fermatean Neutrosophic Rough sets, which characterize Fermatean Neutrosophic rough approximation operators, are investigated.